2015
DOI: 10.1093/toxsci/kfv050
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus laevisOocytes as a Model System for Studying the Interaction Between Asbestos Fibres and Cell Membranes

Abstract: The mode of interaction of asbestos fibres with cell membranes is still debatable. One reason is the lack of a suitable and convenient cellular model to investigate the causes of asbestos toxicity. We studied the interaction of asbestos fibres with Xenopus laevis oocytes, using electrophysiological and morphological methods. Oocytes are large single cells, with a limited ability to endocytose molecular ligands; we therefore considered these cells to be a good model for investigating the nature of asbestos/memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 38 publications
(39 reference statements)
4
16
0
Order By: Relevance
“…In line with our previous study, crocidolite (Croc) exposure affected the electrical membrane properties of oocytes; specifically, the resting membrane potential (RP) and membrane resistance (R m ) were significantly reduced with respect to control (Ctrl), while the current amplitudes activated by both negative and positive voltage steps were increased 2 . Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In line with our previous study, crocidolite (Croc) exposure affected the electrical membrane properties of oocytes; specifically, the resting membrane potential (RP) and membrane resistance (R m ) were significantly reduced with respect to control (Ctrl), while the current amplitudes activated by both negative and positive voltage steps were increased 2 . Fig.…”
Section: Resultssupporting
confidence: 87%
“…Considering that these molecular mechanisms are those that allow the fibers to enter the target cell cytosol and then the nuclear compartment to interfere with the DNA integrity and transcriptional activity, their knowledge is compelling in helping to find new therapeutic approaches for treating exposed subjects. We recently described Xenopus laevis oocytes as a suitable model for studying in detail, the interaction between asbestos fibers and biological cell membranes at the electrophysiological and morphological level 2 . We found that exposure of the oocyte cells to aqueous suspensions of amosite (brown asbestos) or crocidolite (blue asbestos), significantly affected their electrical membrane properties as well as the morphology of the cells, and proposed that the fibers, either by adsorbing onto the cell surface and/or traversing the membrane, somehow created a “pore” through which ion fluxes (most likely Cl − ) could occur to change the resting membrane potential and membrane resistance of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…To learn more about the interactions of NPs with the plasma membrane of the oocytes, we have followed possible changes of its integrity due to exposure to Fe 3 O 4 NPs by Two Electrodes Voltage Clamp (TEVC). With a similar approach, Bernareggi and colleagues 38 have recently evaluated the effects of asbestos fibres on Xenopus oocyte membrane.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that membrane damage allow the influx of extracellular Ca ions into the cell, where it complexes with phosphate groups, ultimately forming crystalline apatite (Trump et al, 1980). In the case of asbestos-induced calcification, it is not entirely clear how the fibers initially interact with cell membranes (Harington et al, 1975;Hill, 1982, 1983;Hesterberg et al, 1986;Malorni et al, 1990;Elferink and Kelters, 1991;Dopp et al, 2000;Nagai and Toyokuni, 2012;Bernareggi et al, 2015), nor is it known why the precipitates form intracellular deposits around asbestos fibers as earlier described by Brody and Hill (Brody and Hill, 1982).…”
Section: Discussionmentioning
confidence: 99%